THE THERAPEUTIC EFFECT OF COMBINED AQUEOUS EXTRACT OF CORIANDER SATIVUM L. AND ALLIUM SATIVUM L. ON THE MERCURIC CHLORIDE INDUCED REPRODUCTIVE TOXICITY IN ADULT MALE RATS - Rajiha A. Al.Naimi Eman H.y. Al.Taae Layth A.M. Alsoufi; Ghusson A.K.Al-Neamah (Basrah Journal of Veterinary Research)
The present study was undertaken to investigate the ability of antioxidants Coriander sativum L . (cilantro ) and Allium sativum L.(garlic ) to protect against mercuric chloride induced reproductive toxicity in male rats .A sub Lethal chronic exposure (0.12mg/kg B.W mercuric chloride )resulted in a decrease of body weight, testicular weight and testosterone hormone with regressed histological properties of testis , epididymis and pre - cancerous changes in epididymis .These changes were ameliorated with the administration of cilantro and garlic .The results of our study suggested that the mentioned antioxidants exert significant protection against mercuric chloride induced male reproductive toxicity and provide a strong evidence for the beneficial role of antioxidant vegetables in prevention of mercury toxicity